2011
DOI: 10.1007/s11242-011-9788-8
|View full text |Cite
|
Sign up to set email alerts
|

Oil Recovery by Low Salinity Water Injection into a Reservoir: A New Study of Tertiary Oil Recovery Mechanism

Abstract: Low salinity water injections for oil recovery have shown seemingly promising results in the case of clay-bearing sandstones saturated with asphaltic crude oil. Reported data showed that low salinity water injection could provide up to 20% pore volume (PV) of additional oil recovery for core samples and up to 25% PV for reservoirs in near wellbore regions, compared with brine injection at the same Darcy velocity. The question remains as to whether this additional recovery is also attainable in reservoirs. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 30 publications
0
32
0
1
Order By: Relevance
“…The fundamental concepts and mechanisms of wettability-controlled morphology transitions could be explored in unprecedented detail. Although the flexibility, reversibility, and reproducibility allow for a thorough exploration of the concepts and mechanisms of wettability-controlled morphology transitions, the origin of contact-angle variations in a reservoir during low-salinity waterflooding must obviously be driven by chemical processes induced by the composition of the injected water (Tang and Morrow 1999;Lager et al 2006Lager et al , 2007Li 2011). Variations in salt content and pH can, in principle, affect the tensions of all interfaces-the oil/water (ow) interface, the water/solid (ws) interface, and the oil/solid (os) interface.…”
Section: Resultsmentioning
confidence: 99%
“…The fundamental concepts and mechanisms of wettability-controlled morphology transitions could be explored in unprecedented detail. Although the flexibility, reversibility, and reproducibility allow for a thorough exploration of the concepts and mechanisms of wettability-controlled morphology transitions, the origin of contact-angle variations in a reservoir during low-salinity waterflooding must obviously be driven by chemical processes induced by the composition of the injected water (Tang and Morrow 1999;Lager et al 2006Lager et al , 2007Li 2011). Variations in salt content and pH can, in principle, affect the tensions of all interfaces-the oil/water (ow) interface, the water/solid (ws) interface, and the oil/solid (os) interface.…”
Section: Resultsmentioning
confidence: 99%
“…Gravimetric separation and air floatation then produce bitumen froths, which contain significant amounts of water and solids that must be removed before bitumen upgrading. Therefore, there are several studies dedicated to i) the interactions between bitumen and clays through zeta potential distribution measurement [292][293][294], AFM [292], and model systems such as particles coated with asphaltenes [295] or model water-in-hydrocarbon emulsions [296] and ii) the removal of the solids from the bitumen before the upgrading process [297][298][299].…”
Section: The Asphalt-clay Binary Systemmentioning
confidence: 99%
“…Several other studies [2,52,53] have shown that in the absence of multivalent ions, positive benefits are still observed when the brine salinity is reduced. Li [54] reported higher incremental recovery in the absence of initial water saturation during secondary and tertiary injection mode for the weakly water-wet core. They concluded that with same rock wettability, oil recovery increased with lower initial water saturation while at same initial water saturation, oil recovery increased with reduced water-wetness.…”
Section: Sandstone Rocksmentioning
confidence: 97%